2018
DOI: 10.1136/annrheumdis-2018-213403
|View full text |Cite|
|
Sign up to set email alerts
|

Methotrexate and BAFF interaction prevents immunization against TNF inhibitors

Abstract: ObjectivesTNF inhibitors (TNFi) can induce anti-drug antibodies (ADA) in patients with autoimmune diseases (AID) leading to clinical resistance. We explored a new way of using methotrexate (MTX) to decrease this risk of immunisation.MethodsWe treated BAFF transgenic (BAFFtg) mice, a model of AID in which immunisation against biologic drugs is high, with different TNFi. We investigated the effect of a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…MTX in the presence of higher (and not lower) BAFF levels negatively impacted vaccine response to seasonal influenza vaccination, further supporting the counter-intuitive, paradoxical immune suppressive effect of BAFF in the presence of MTX. This hypothesis-driven study is a first proof of concept to confirm the recent basic-translational finding by Bitoun et al that provides a biological explanation of MTX–BAFF interaction that induces a tolerance to biological disease modifying antirheumatic drugs (ie, TNF inhibitor) and new antigens such as vaccination by generating immune suppressive adenosine and regulatory B cells 5. This study supports that BAFF–MTX interaction at the time of antigen challenge is critical and that immune modulation by DMARDs depends on host immune factors.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…MTX in the presence of higher (and not lower) BAFF levels negatively impacted vaccine response to seasonal influenza vaccination, further supporting the counter-intuitive, paradoxical immune suppressive effect of BAFF in the presence of MTX. This hypothesis-driven study is a first proof of concept to confirm the recent basic-translational finding by Bitoun et al that provides a biological explanation of MTX–BAFF interaction that induces a tolerance to biological disease modifying antirheumatic drugs (ie, TNF inhibitor) and new antigens such as vaccination by generating immune suppressive adenosine and regulatory B cells 5. This study supports that BAFF–MTX interaction at the time of antigen challenge is critical and that immune modulation by DMARDs depends on host immune factors.…”
supporting
confidence: 73%
“…A possible candidate is B-cell activating factor (BAFF), which promotes B-cell activation and differentiation for antibody production 4. When patients with RA received anti-TNF treatment, a high BAFF serum level prevented formation of antidrug antibody in patients taking MTX but not those who did not 5. Thus, in the presence of MTX, BAFF may exert a paradoxical anti-inflammatory effect.…”
mentioning
confidence: 99%
“…The main immunosuppressants prescribed in the cohort were methotrexate (MTX), azathioprine, and leflunomide. A mechanism of MTX-induced tolerization was recently proposed by ABIRISK collaborators, who demonstrated in BAFF (B-cell activated factor) transgenic mice that high levels of BAFF were necessary for MTX-induced tolerization and confirmed it in the anti-TNF-treated patients of the ABIRISK prospective study [ 21 ]. BAFF induced an increase in the CD73 enzyme on the B cell surface, which catalyzes conversion of extracellular AMP (Adenosine MonoPhosphate) into the immunosuppressant adenosine.…”
Section: Discussionmentioning
confidence: 89%
“…Rituximab is a chimeric monoclonal antibody that has been approved for multiple types of malignancy and autoimmune diseases. Methotrexate, an inhibitor of dihydrofolate reductase, impacts rapidly dividing T and B cells (28,29). Experience from rheumatologic disorders has shown that the addition of methotrexate with other biological therapy has prevented the development of ADA against therapeutic proteins (30).…”
Section: Introductionmentioning
confidence: 99%